Low Carbon-Development Strategy for the Oil and Gas Industry - Liu, Fei (International Journal of Natural Resources and Environmental Studies, 2024)
As an important source of carbon emissions in China, promoting the low-carbon development of the oil and gas industry is the only way to achieve the "dual-carbon" goal, and is also an important goal in the implementation of the "four revolutions and one co-operation" energy strategy. Therefore, this paper will explore the optimal path for low-carbon development of the oil and gas industry from the perspective of the four revolutions, one cooperation and ethical environment, with a view to accelerating the transformation and upgrading of the oil and gas industry and achieving high-quality development.